Structural insights for neutralization of BA.1 and BA.2 Omicron variants by a broadly neutralizing SARS-CoV-2 antibody - Kumar, Sanjeev; Patel, Anamika; Lai, Lilin; Chakravarthy, Chennareddy; Valanparambil, Rajesh; Davis-Gardner, Meredith E; Edara, Venkata Viswanadh; Linderman, Susanne; Reddy, Elluri Seetharami; Gottimukkala, Kamalvishnu; Nayak, Kaustuv; Bajpai, Prashant; et al. (bioRxiv, 2022)
The SARS-CoV-2 BA.1 and BA.2 (Omicron) variants contain more than 30 mutations within the spike protein and evade therapeutic monoclonal antibodies (mAbs). Here, we report a receptor binding domain (RBD) targeting human antibody (002-S21F2) that effectively neutralizes live viral isolates of SARS-CoV-2 variants of concern (VOCs) including Alpha, Beta, Gamma, Delta, and Omicron (BA.1 and BA.2) with IC50 ranging from 0.02 – 0.05 ug/ml. This near germline antibody 002-S21F2 has unique genetic features that are distinct from any reported SARS-CoV-2 mAbs. Structural studies of the full-length IgG in complex with spike trimers (Omicron and WA.1) reveal that 002-S21F2 recognizes an epitope on the outer face of RBD (class-3 surface), outside the ACE2 binding motif and its unique molecular features enable it to overcome mutations found in the Omicron variants. The discovery and comprehensive structural analysis of 002-S21F2 provide valuable insight for broad and potent neutralization of SARS-CoV-2 Omicron variants BA.1 and BA.2. Competing Interest Statement The International Centre for Genetic Engineering and Biotechnology, New Delhi, India, Emory Vaccine Center, Emory University, Atlanta, USA, Indian Council of Medical Research, India and Department of Biotechnology, India have filed a provisional patent application on human monoclonal antibodies mentioned in this study on which A.C., S.K., M.K.K., and A.S. are inventors (Indian patent 202111052088). M.S.S. serves on the advisory board for Moderna and Ocugen. All other authors declare no competing interests.